Everyday micro- resistances and horizons of radical solidarity, care, and mutualism - Kokkinidis, George; Checchi, Marco (My University, 2023)
Although resistance is traditionally conceived as oppositional and reactive, we propose to follow those everyday resistant practices that create alternative organisations and horizons of change. Drawing on data collected through a range of qualitative methodologies (semi-structured interviews, participant observation, and informal group conversations) from KIA, a social and solidarity clinic in Greece, and Ri.Maflow, a recuperated factory in Italy, we explore the microphysics of resistance at work and its transformative potential. We reflect on how a social clinic evolves from a healthcare initiative to a health community and a space of wider social experimentation that is questioning the traditional hierarchical structure of the medical apparatus. Or how a recuperated factory is more than a reaction to unemployment, as it reinvents work, autonomy, and self-management within the walls of the warehouse and in its relation with the wider ecology of its community. We want to emphasise how these resistances are not simply a reaction against the loss of social and economic infrastructures due to austerity, but active practices of solidarity that experimentally engage with creation with often unintentional and unanticipated outcomes.